Manajemen Berbasis Sekolah atau Peran Komite di SD - Kasmawati, Kasmawati; Ariska, Vira; Zulkhintania, Aurelly; Ananda, Rizki; Kuswari, Nyi Euis Diah; Suryanto, MHD.Hajad (EduInovasi: Journal of Basic Educational Studies, 2026)
School-Based Management (SBM) is an educational management model that grants schools the authority to independently manage their resources while involving all members of the school community and the wider society. The implementation of SBM aims to improve the quality of education through participatory, transparent, accountable, effective, and efficient decision-making processes. In its implementation, the school committee plays a strategic role as a partner of the school by providing recommendations, support, supervision, and serving as a mediator between the school and the community. At the elementary school level, the existence of the school committee is highly important in supporting educational programs, increasing community participation, and promoting good school governance. This article discusses the concept of School-Based Management, its implementation principles, the functions and roles of school committees, the challenges they face, and strategies for strengthening partnerships between schools and school committees in improving the quality of primary education.